Toward French and Italian Language Validations of the Conspiracy Mentality Scale (CMS) - Ana Stojanov; Annegret Hannawa (Measurement Instruments for the Social Sciences, 2023)
The growing scientific interest in conspiracy beliefs calls for validated measures of conspiracy mentality, the tendency to believe any conspiracy theory. In this study, we validate a French and Italian version of the Conspiracy Mentality Scale (CMS). French (N = 160) and Italian (N = 114) speaking residents of Switzerland filled out a questionnaire, including measures of the need for social validation, compliance with COVID-19 preventive measures, perceived severity of the pandemic, and functional literacy. The two-dimensionality of the scale (conspiracy theory ideation and skepticism) was validated by confirmatory factor analysis. As predicted, conspiracy theory ideation was negatively related to functional literacy and compliance with pandemic control measures, and positively related to social validation. Measurement invariance indicated metric, scalar, residual and strucutral equivalence across the two samples. We conclude that the French and Italian versions of the CMS lend a valid assessment of people’s general tendency to believe conspiracy theories.